A new genus and species of burrower bugs (Heteroptera: Cydnidae) from the mid-Cretaceous Burmese amber - Wang, Yijia; Du, Sile; Yao, Yunzhi; Ren, Dong (Zootaxa, 2019)
A new genus and species of Cydnidae, Punctacorona triplosticha gen. et sp. nov. (Heteroptera: Pentatomomorpha) is described and illustrated from Myanmar amber. This new genus is established based on its forewing anterior margin angulated, clavus narrow, with three rows of distinct punctures, metapleuron neighboring to posterior margin of evaporatorium carinate. A comparison between the new species and the Chilamnestocoris mixtus Lis et al. 2018 from Myanmar is provided.